A hybrid grid connected solar-fuel cell energy converter for common household load - Madiwanan, Prakash (2010)
Solar energy has good prospects for both isolated load and grid-connected. Solar cell power source should be integrated with other supplementary power source whether is operate in a standalone or grid-connected mode. The fuel cell energy has a great potential for being coordinated with the solar panel to smooth out the solar panel power’s fluctuation. Therefore, a hybrid grid-connected solar-fuel cell energy converter can be very attractive in such a case for household application. The project will start from literature research of solar cell, fuel cell, and maximum power point tracking (MPPT), DC-DC converter and DC-AC inverter.